Upaya guru dalam meningkatkan kemampuan kerja sama siswa selama pembelajaran melalui penerapan metode diskusi - Sovia Clara Wau; Wiputra Cendana (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
cooperation is one of the skills required for students to live a bonded life. Every social being has needs and the reality is more cooperation between students is still needed. It was still in practice to found that there is little cooperation between students in the class during study. The aim of this study was to expresent a teacher's efforts to enhance the ability of student cooperation teacher as the guide in the teaching and learning activity using discussion learning method. Through application of increased cooperation methods from two to four groups capable of demonstrating the interaction between students in completing a task. This was descriptive qualitative methods. Through application of increased cooperation methods from two to four groups capable of demonstrating the interaction between students in completing a task. The research methods in this paper use descriptive qualitative methods. The teacher's efforts by applying a method of discussion enhance the students' ability to cooperate during the study. The advice for the writer will be that the application of this method may be more frequent and of other subjects, as well as that of learning other ways to enhance cooperation.